Performance study of a hybrid photovoltaic and solar water disinfection system considering climatic variations over a year. (15th July 2017) - Pichel, N.; Vivar, M.; Fuentes, M.
Graphical abstract: Highlights: A hybrid photovoltaic and water purification system was tested under different UV and temperature conditions. The water purification reactor did not affect the final energy output of the SOLWAT system. SOLWAT achieved the highest disinfection results for E. coli, total coliforms and C. perfringens . High UV and high/low ambient temperatures would be the ideal operation conditions for the SOLWAT. Abstract: A hybrid photovoltaic and solar water purification system (SOLWAT) was tested considering climatic variations over a year. The solar disinfection and electrical performance was assessed using natural water with wild bacteria strains of E. coli, total coliforms, Enterococcus spp. and Clostridium perfringens (including spores). After 6 h of sun exposure the SOLWAT system achieved the highest bacteria disinfection for E. coli, total coliforms and C. perfringens in relation to the conventional PET bottle, and C. perfringens was identified as the most resistant microorganism since its complete inactivation was never reached. Electrical results showed that the total energy output of the SOLWAT system designed and tested was not affected by the water disinfection reactor located above the PV module in relation to a single PV module, mainly because of the compensating effect of lower operation temperature of the PV module within the SOLWAT system vs. slightly reduced solar irradiance received. Finally, the ideal operation conditions for the SOLWAT system would be to work with high ambient temperatures and UV radiation or low ambient temperatures combined with high UV levels, being the worst conditions for its operation mild temperatures and mild/low UV levels.